Influence of Bio-fertilization on Physical and Biochemical Parameters of Grapefruit Saplings Citrus paradisi Macfad. Under Salt Stress - Sabaa J. Abdulkadhim (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The experiment was conducted in a partially shaded area (50% shade-net) throughout the 2023 growing season. This experiment aimed to know the role of biofertilization in increasing the ability of grapefruit seedlings to tolerate salt stress. Biofertilizers were applied with four levels (without biofertilizers, mycorrhizal fungi, bacteria, and mycorrhizae + bacteria). 20 g of mycorrhizal fungi were added near the saplings roots. 20 ml of bacteria were injected into the soil and in contact with the root zone. Adding 20 g of mycorrhizal fungi + 20 ml of bacteria to the pots soil at the same time and near the roots of the saplings carried out the mycorrhizae + bacteria treatment. Saplings were watered with three concentrations of saline water (2¸ 4¸ and 6 ds.m-l NaCl2). The results indicated that at the 6 ds.m-1 level, there was a reduction in physical and biochemical parameters. This decrease is accompanied with an increase in proline, Cl%, and Na%. The integration of mycorrhizal fungus and Azospirillum bacteria showed a significant superiority in root and shoot growth. Biofertilization caused increase the content of   carbohydrates, protein, and chlorophyll in plants. Also, obtained result showed increase the content of some macro and micro- elements in plants such as N, P, K, Zn and Fe. While the percentage of Cl and Na and proline content decreased, resulting reduced the damages of salt stress.